Assessment of regulatory quality in electronic communications in South Africa - Silaule, Goodman (My University, 2014)
After enactment of the Electronic Communication Act of 2005, there has been increased regulation in the electronic communications sector. The purpose of this study is to investigate how ICASA ensured regulatory quality when formulating regulations. Regulatory quality is an effective way of ensuring that new or amended regulations achieve they intended objectives. Failure to address regulatory quality may result in ineffective and costly regulations that negatively impact the electronic communications sector. This study revealed that there are regulatory quality gaps in the regulatory process followed by ICASA. The study established that there was lack of transparency and consistency in the process followed by ICASA when formulating regulations. The regulatory decisions made by ICASA were not evidence based as no ex-ante regulatory impact assessment was conducted. The regulatory environment within which ICASA operated was not conducive to enabling regulatory quality. The main factors contributing to an unsuitable regulatory environment were identified as prescriptive sector legislation, ineffective institutional arrangements, and ICASAs‘ lack of the capacity and resources.
Keywords: Independent Communications Authority of South Africa.; Telecommunication policy; South Africa; Electronic communications; Regulation